2012
DOI: 10.1016/j.pdpdt.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Safety and long term efficacy of porfimer sodium photodynamic therapy in locally advanced biliary tract carcinoma

Abstract: Background In patients with unresectable cholangiocarcinoma, photodynamic therapy (PDT) with porfimer sodium promotes biliary drainage and may improve survival and quality of life. Aim To prospectively evaluate the safety and efficacy of PDT in patients with locally advanced biliary tract carcinoma. Methods Eligible patients had unresectable, histologically confirmed disease, a Karnofsky performance status of ≥30% and life expectancy >12 weeks. Patients received 2mg/kg i.v. of porfimer sodium, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
0
15
1
2
Order By: Relevance
“…13 In our study, the most frequent adverse event was cholangitis, experienced by almost a quarter of our study population (21/88). This is relatively high compared to previous data on PDT 14,15 and, of course, might not be associated with PDT alone but also with the underlying malignant biliary obstruction or the biliary manipulation during ERC. However, occurring without any obvious association with other clinical parameters and observed with the same frequency among all participating centers, cholangitis might be mainly attributed to local inflammation after PDT.…”
Section: Discussioncontrasting
confidence: 56%
“…13 In our study, the most frequent adverse event was cholangitis, experienced by almost a quarter of our study population (21/88). This is relatively high compared to previous data on PDT 14,15 and, of course, might not be associated with PDT alone but also with the underlying malignant biliary obstruction or the biliary manipulation during ERC. However, occurring without any obvious association with other clinical parameters and observed with the same frequency among all participating centers, cholangitis might be mainly attributed to local inflammation after PDT.…”
Section: Discussioncontrasting
confidence: 56%
“…Common adverse events after PDT include acute cholangitis, pancreatitis, hematobilia, liver abscess, and skin photosensitivity reactions. Most of these are ERCP-or PTCS-related complications, including a PDT-specific skin phototoxicity [8][9][10]20]. A meta-analysis of 10 studies found a pooled odds ratio for post-intervention cholangitis in the PDT group vs. stent group of only 0.57 (95% CI 0.35-0.94) and a pooled incidence of photosensitivity secondary to PDT of only 10.51% (95% CI 6.94-14.72%), reactions that were self-limiting [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, PDT is expensive and time-consuming. In addition to complications, including hemobilia of the stenting site and photosensitivity, one multicenter study demonstrated that patients who received PDT with stenting had a 60% increased mortality risk with poorer overall survival compared to that of stenting alone [ 14 ]. A safer and more effective method to resolve HCC-BDI is therefore needed.…”
Section: Discussionmentioning
confidence: 99%